UAV-Assisted IRS System With Energy Harvesting: Enhanced Reliability in Critical Scenarios for 5G/6G Wireless Communication - Pankaj Kumar; Santhosha Kamath; Sam Darshi; Jen-Yi Pan; Muhammad Iqbal; Samar Shailendra; Vijay Mohan (IEEE Access)
This paper proposes an UAV-assisted intelligent reflecting surface (IRS) system for improving the network performance between ground-to-ground (G2G) users in 5G/6G wireless communication. This work may be applicable for packet delivery in bustling urban areas, especially where G2G links are in deep fade. For energizing the IRS elements and controlling the processing units of the UAV, radio-frequency (RF)-based energy harvesting (EH) is proposed at UAV, where the dynamic power splitting factor depends on the height-dependent Nakagami-m shaping parameter (m). The mathematical framework for the proposal includes the height-dependent Nakagami-m fading to represent small-scale fading and height-dependent path-loss exponent to model large-scale fading. We develop the expression for spectral efficiency and derive a closed-form expression of an outage probability for the proposed scenario by considering Nakagami-m channel among A2G links. The analytical results are validated with simulation results, and the work is compared with the existing state-of-the-art.